ChemInform Abstract: Total Syntheses of Rubiginone A2, C2, and Fujianmycin A. Issue 48 (2nd December 2014) - Vanga, Devendar G.; Kaliappan, Krishna P.
Abstract Rubiginone A2 (Ia), rubiginone C2 (Ib) and fujianmycin A (Ic) are synthesized enantioselectively starting from ((2R, 3R)‐3‐methyloxiran‐2‐yl)methanol in 14, 12 and 16% yield, respectively.